Differential stress reaction of human colon cells to oleic-acid-stabilized and unstabilized ultrasmall iron oxide nanoparticles - MOVIA, DANIA; PRINA MELLO, ADRIELE (My University, 2014)
Therapeutic engineered nanoparticles (NPs), including ultrasmall superparamagnetic iron oxide (USPIO) NPs, may accumulate in the lower digestive tract following ingestion or injection. In order to evaluate the reaction of human colon cells to USPIO NPs, the effects of non-stabilized USPIO NPs (NS-USPIO NPs), oleic-acid-stabilized USPIO NPs (OA-USPIO NPs), and free oleic acid (OA) were compared in human HT29 and CaCo2 colon epithelial cancer cells. First the biophysical characteristics of NS-USPIO NPs and OA-USPIO NPs in water, in cell culture medium supplemented with fetal calf serum, and in cell culture medium preconditioned by HT29 and CaCo2 cells were determined. Then, stress responses of the cells were evaluated following exposure to NS-USPIO NPs, OA-USPIO NPs, and free OA. No modification of the cytoskeletal actin network was observed. Cell response to stress, including markers of apoptosis and DNA repair, oxidative stress and degradative/autophagic stress, induction of heat shock protein, or lipid metabolism was determined in cells exposed to the two NPs. Induction of an autophagic response was observed in the two cell lines for both NPs but not free OA, while the other stress responses were cell- and NP-specific. The formation of lipid vacuoles/droplets was demonstrated in HT29 and CaCo2 cells exposed to OA-USPIO NPs but not to NS-USPIO NPs, and to a much lower level in cells exposed to equimolar concentrations of free OA. Therefore, the induction of lipid vacuoles in colon cells exposed to OA utilized as a stabilizer for USPIO NPs is higly amplified compared to free OA, and is not observed in the absence of this lipid in NS-USPIO NPs.
PUBLISHED
Keywords: Apoptosis; Caco-2 Cells; Heat-Shock Proteins; HT29 Cells; Humans; Lipids; Magnetite Nanoparticles; Oleic Acid; Particle Size; Stress, Physiological; Vacuoles; Apoptosis; Caco-2 Cells; Heat-Shock Proteins; HT29 Cells; Humans; Lipids; Magnetite Nanoparticles; Oleic Acid; Particle Size; Stress, Physiological; Vacuoles; Cancer; Nanoscience & Materials; CANCER TREATMENT; NanoMedicine; Nanosafety; Translational Nanomedicine